Preparation method of Co3O4 nanocubes embedded with ZnO nanofiber tubes and their gas-sensing applications

CN118005067BActive Publication Date: 2026-10-30ANHUI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311859353.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-30
Publication Date
2026-10-30
Estimated Expiration
2043-12-30

AI Technical Summary

Technical Problem

[0003]针对现有技术中的上述问题,本发明提供一种Co3O4纳米立方体嵌入ZnO纳米纤维管的制备方法和应用,以解决现有ZnO作为乙苯传感纳米材料的选择性差、灵敏度低的诸多技术问题

Benefits of technology

[0016]1、本发明使用同轴静电纺丝技术将多孔Co3O4纳米立方体嵌入ZnO纳米纤维管中,形成独特的异质结,提供丰富的活性位点,可以有效地提高对乙苯的吸附能力,提高气体检测的灵敏度,从而提高乙苯的气体传感性能,使得检测浓度范围为0.5~100ppm,实现宽浓度范围乙苯的高灵敏响应,通过测试发现,本发明制备的多孔Co3O4纳米立方体嵌入ZnO纳米纤维管使得气敏传感器的气敏性能得到了显著提高,简单地说,当Co3O4/ZnO NTs的传感器暴露在空气中时,空气中O2分子将被吸附在Co3O4/ZnO NTs的表面,并从Co3O4/ZnO NTs表面的导带捕获电子,且电离成O-,从而降低导带中自由电子的浓度,形成耗尽层。当传感器暴露于乙苯中,吸附在Co3O4/ZnO NTs表面的乙苯分子将提供电子还原氧离子(O-),然后将捕获的电子释放回Co3O4/ZnO NTs的导带,从而增加自由电子的浓度,缩小耗尽层的宽度,从而降低传感器的电阻。当传感器从乙苯返回空气时,Co3O4/ZnO NTs表面的乙苯分子开始解吸,Co3O4/ZnO NTs的导带吸收电子,降低了Co3O4/ZnO NTs导带中自由电子的浓度,从而增加了传感器电阻。进而实现了对乙苯的高灵敏度响应,最终有效地解决了气敏传感器对乙苯一直以来固有的灵敏度较低问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118005067B_ABST
    Figure CN118005067B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and gas-sensitive application of Co3O4 nano-cube embedded in a ZnO nanofiber tube, relates to the technical field of ethylbenzene sensing nanomaterials, and is characterized in that the nanofiber tube is obtained by calcining a product obtained by coaxial electrospinning with ZIF-67 organic solution as an inner shaft solution and with a zinc salt organic solution as an outer shaft solution, and polyvinylpyrrolidone is added in the inner shaft solution and the outer shaft solution. The application uses the coaxial electrospinning technology to embed the porous Co3O4 nano-cube into the ZnO nanofiber tube, forms a unique heterojunction, provides abundant active sites, can effectively improve the adsorption capacity for ethylbenzene, improves the sensitivity of gas detection, thereby improves the gas sensing performance of ethylbenzene, makes the detection concentration range 0.5-100 ppm, and realizes the high-sensitivity response of ethylbenzene in a wide concentration range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ethylbenzene sensing nanomaterials technology, specifically to a method for preparing Co3O4 nanocubes embedded with ZnO nanofiber tubes and their applications. Background Technology

[0002] Volatile organic compounds (VOCs) are widely used or released in industrial engineering, transportation, and household activities. Many VOCs are toxic to humans (carcinogenic, mutagenic, or teratogenic) and can cause air pollution. Currently, BTEX (benzene, toluene, ethylbenzene, and xylene) are receiving widespread attention due to their frequent high-concentration releases in urban outdoor and indoor environments and their health hazards. The monitoring of ethylbenzene in daily life has attracted widespread attention, and researchers have done a great deal of work on ethylbenzene detection. However, finding a sensing material that is easy to synthesize and has good sensitivity and selectivity for ethylbenzene remains a challenge for the scientific community. The production of high-performance ethylbenzene sensors for environmental monitoring and human health protection is extremely important and urgent. Currently, zinc oxide (ZnO), as a typical n-type metal oxide semiconductor (with a band gap of 3.22-3.5 eV), is a relatively promising ethylbenzene sensing material. However, ZnO's weak selectivity and low sensitivity hinder its practical application as a high-performance gas sensor. Generally, the sensing performance of sensing materials can be improved by adjusting their morphology and loading with noble metals. In order to further expand the practical application of ZnO as a high-performance gas sensor, adjusting its morphology and loading with noble metals are relatively feasible means. Therefore, improving the selectivity, sensitivity and operating temperature of ZnO as an ethylbenzene sensing nanomaterial through morphology adjustment and loading with noble metals is the focus of this study. Summary of the Invention

[0003] To address the aforementioned problems in the prior art, this invention provides a method for preparing and applying Co3O4 nanocubes embedded with ZnO nanofiber tubes, thereby solving many technical problems such as poor selectivity and low sensitivity of existing ZnO as an ethylbenzene sensing nanomaterial.

[0004] The technical solution adopted in this invention is as follows:

[0005] The nanofiber tubes are made by embedding ZnO in Co3O4 nanocubes. The nanofiber tubes are obtained by simultaneously spinning a porous Co3O4 nanocube organic solution as the inner axis solution and a zinc salt organic solution as the outer axis solution using coaxial electrospinning technology. The product is then calcined. Polyvinylpyrrolidone is added to both the inner axis solution and the outer axis solution.

[0006] Preferably, the porous Co3O4 nanocubes have a particle size of 200–300 nm.

[0007] Preferably, the width of the nanofiber tube is 100-200 nm and the length is 100-500 μm.

[0008] Preferably, the solvent for the inner axis solution and the outer axis solution is N,N dimethylformamide.

[0009] The preparation method of the Co3O4 nanocube embedded ZnO nanofiber tube according to any one of the above methods includes the following steps: dispersing ZIF-67 nanocubes in an organic solution, adding polyvinylpyrrolidone and stirring to mix, denoted as the inner axis solution; adding Zn... 2+ Dispersed in an organic solution, polyvinylpyrrolidone was added and stirred until homogeneous, and this was designated as the outer axis solution. The inner and outer axis solutions were spun simultaneously using coaxial electrospinning technology, and aluminum foil was used to collect the fibers. The product was then calcined in air to obtain hollow porous Co3O4 / ZnO nanofiber tubes.

[0010] Furthermore, the stirring time for the inner shaft solution and the outer shaft solution after adding polyvinylpyrrolidone is 12 hours.

[0011] Furthermore, in the inner-axis solution and the outer-axis solution, ZIF-67 nanocubes and Zn 2+ The molar ratio is 0.06 to 0.33:1.

[0012] Furthermore, in the coaxial electrospinning process, the spinning high voltage is 18kV, the distance is 15cm, the outer shaft pushing speed of the electrospinning reaction is 0.0003mm / s, the inner shaft pushing speed is 0.0002mm / s, and the reaction humidity is controlled at 20% to 40%.

[0013] Furthermore, the calcination temperature is 500℃, the calcination time is 120 min, and the heating rate is 2℃ / min.

[0014] The above-mentioned Co3O4 nanocube embedded ZnO nanofiber tubes are used as materials for preparing gas sensors in ethylbenzene detection.

[0015] In summary, compared with the prior art, the present invention has the following advantages and beneficial effects:

[0016] 1. This invention utilizes coaxial electrospinning technology to embed porous Co3O4 nanocubes into ZnO nanofiber tubes, forming a unique heterojunction that provides abundant active sites. This effectively enhances the adsorption capacity for ethylbenzene, improves the sensitivity of gas detection, and thus improves the gas sensing performance of ethylbenzene, enabling a detection concentration range of 0.5–100 ppm and achieving high sensitivity response over a wide concentration range. Testing revealed that the embedded porous Co3O4 nanocubes prepared in this invention significantly improve the gas sensing performance of the gas sensor. Simply put, when the Co3O4 / ZnO NTs sensor is exposed to air, O2 molecules in the air are adsorbed onto the surface of the Co3O4 / ZnO NTs, and electrons are captured from the conduction band of the Co3O4 / ZnO NTs surface, ionizing into O2. - This reduces the concentration of free electrons in the conduction band, forming a depletion layer. When the sensor is exposed to ethylbenzene, ethylbenzene molecules adsorbed on the surface of Co3O4 / ZnO NTs will donate electrons to reduce oxygen ions (O3O4 / ZnO NTs). - The trapped electrons are then released back into the conduction band of Co3O4 / ZnO NTs, increasing the concentration of free electrons, reducing the width of the depletion layer, and thus lowering the sensor's resistance. When the sensor returns from ethylbenzene to air, ethylbenzene molecules on the surface of the Co3O4 / ZnO NTs begin to desorb, and the conduction band of the Co3O4 / ZnO NTs absorbs electrons, reducing the concentration of free electrons in the conduction band and thus increasing the sensor's resistance. This achieves a high-sensitivity response to ethylbenzene, effectively solving the inherent problem of low sensitivity of gas sensors to ethylbenzene.

[0017] 2. In this invention, since the Co3O4 nanocubes themselves have a porous structure, they can still maintain the shape formed before calcination after high-temperature calcination. The particle size is also controlled at about 100-200 nm after calcination, and they are uniformly dispersed, which can increase the adsorption specific surface area. Therefore, the nanomaterials prepared by the preparation method of this invention have a significant effect on improving the sensitivity of the sensor.

[0018] 3. The nano-sized Co3O4 and ZnO of this invention are both inexpensive and readily available, resulting in low preparation costs and easy product promotion. Attached Figure Description

[0019] Figure 1These are scanning electron microscope (SEM) images of the porous Co3O4 nanocubes before and after calcination in Example 1 of this invention, and of the porous Co3O4 nanocubes embedded in ZnO nanofiber tubes before and after calcination in Example 2. (a) is an SEM image of the porous Co3O4 nanocubes before calcination; (b) is an SEM image of the porous Co3O4 nanocubes after calcination; (c) is an SEM image of the porous Co3O4 nanocubes embedded in ZnO nanofiber tubes before calcination; and (d) is an SEM image of the porous Co3O4 nanocubes embedded in ZnO nanofiber tubes after calcination.

[0020] Figure 2 These are scanning electron microscope images of the nanofiber tubes prepared in Comparative Example 1 and various embodiments of the present invention, wherein (a) is a porous hollow ZnO nanofiber tube prepared in Comparative Example 1; (b) is a porous Co3O4 nanocube embedded ZnO nanofiber tube prepared in Example 3; (c) is a porous Co3O4 nanocube embedded ZnO nanofiber tube prepared in Example 4; (d) is a porous Co3O4 nanocube embedded ZnO nanofiber tube prepared in Example 2; (e) is a porous Co3O4 nanocube embedded ZnO nanofiber tube prepared in Example 5; and (f) is a porous Co3O4 nanocube embedded ZnO nanofiber tube prepared in Example 6.

[0021] Figure 3 The images shown are transmission electron microscope images of the porous Co3O4 nanocube embedded ZnO nanofiber tube obtained in Example 2 of this invention. The left image is a 100nm microscopic image, and the right image is a 5nm microscopic image.

[0022] Figure 4 The image shows the X-ray photoelectron spectroscopy (XPS) analysis of the porous Co3O4 nanocube embedded with ZnO nanofiber tube obtained in Example 2 of this invention.

[0023] Figure 5 The X-ray powder diffraction pattern of the porous Co3O4 nanocube embedded with ZnO nanofiber tube obtained in Example 2 of the present invention.

[0024] Figure 6 The graph shows a comparison of the sensitivity of the nanomaterials obtained in Examples 2-6 and Comparative Examples 1 and 2 to 50 ppm ethylbenzene at different temperatures.

[0025] Figure 7The selective radar diagram and stability diagram of the porous Co3O4 nanocube embedded ZnO nanofiber tube and the ZnO porous nanofiber tube obtained in Example 2 of the present invention are shown. (a) Sensitivity response radar diagram for different gases when used as a gas sensor; (b) Stability test diagram of porous Co3O4 nanocube embedded ZnO nanofiber tube for 50 ppm ethylbenzene when used as a gas sensor. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings, embodiments, and verification examples. It should be understood that the specific embodiments and verification examples described herein are only for explaining the invention and are not intended to limit the invention; that is, the described embodiments are merely some embodiments of the invention, and not all embodiments.

[0027] The term "embodiment" used herein, as an example, is not necessarily to be construed as superior to or better than other embodiments. Performance testing in these embodiments, unless otherwise specified, employs conventional testing methods in the art. The terminology used in this invention is merely for describing particular implementations and is not intended to limit the scope of the disclosure.

[0028] Unless otherwise stated, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; other raw materials, reagents, test methods and techniques not specifically mentioned herein refer to raw materials and reagents commonly used by one of ordinary skill in the art, as well as commonly employed test methods and techniques.

[0029] Example 1

[0030] This embodiment provides a porous Co3O4 nanocube, the preparation process of which is as follows:

[0031] (1) Dissolve 4.54 g of dimethylimidazole in 70 mL of deionized water and heat in a water bath at 40 °C for 20 min, and record this as solution A; dissolve 0.29 g of cobalt nitrate hydrate and 0.03 g of CTAB in 25 mL of deionized water and stir thoroughly, and record this as solution B; quickly pour solution A into solution B and stir in a water bath at 40 °C for 20 min. Transfer the reaction solution into a centrifuge tube and centrifuge at 8500 rpm. Wash with ethanol 3 times and N,N dimethylformamide 3 times until the supernatant is colorless and transparent. Dry under vacuum at 60 °C overnight to finally obtain the calcined precursor of cubic hollow Co3O4, namely ZIF-67.

[0032] (2) The product obtained above was calcined in air at a temperature of 500°C and a rate of 2°C / min for 120 min. After cooling to room temperature, a black porous Co3O4 nanocube structure was obtained.

[0033] The porous Co3O4 nanocubes prepared in Example 1 were examined by scanning electron microscopy before and after calcination, and the results are as follows: Figure 1 As shown: (Refer to) Figure 1 (a) The figure shows the obtained porous Co3O4 nanocubes before calcination. They exhibit a cubic morphology, smooth surface, uniform particle size, and are controlled to be around 250 nm. (Refer to...) Figure 1 (b) As shown in the figure, the porous Co3O4 nanocubes have a particle size of about 100 nm and a rough, porous surface.

[0034] Example 2

[0035] This embodiment provides a porous Co3O4 nanocube embedded with ZnO nanofiber tube, the preparation process of which is as follows:

[0036] (1) Add 1.5 mmol of zinc nitrate hexahydrate to 4.5 mL of N,N dimethylformamide, stir to dissolve, and then add 0.9 g of polyvinylpyrrolidone, which is called the outer axis solution; add 0.3 mmol of ZIF-67 prepared in Example 1 to 4.5 mL of N,N dimethylformamide, sonicate for 10 min, stir for 10 min, and then add 0.9 g of polyvinylpyrrolidone, which is called the inner axis solution. The rotation speed is 120 rpm / min, and the mixture is stirred for 12 h.

[0037] (2) The two solutions prepared above are spun using coaxial electrospinning technology under the conditions of humidity of 20% to 40%, voltage of 18kV, outer shaft speed of 0.0003mm / s and inner shaft speed of 0.0002mm / s.

[0038] (3) The nanofiber tubes obtained above were calcined in air at a temperature of 500℃ for 120 min at a heating rate of 2℃ / min. After cooling to room temperature, porous Co3O4 nanocubes embedded with ZnO nanofiber tubes were obtained, referred to as 0.3Co / Zn.

[0039] The porous Co3O4 nanocubes embedded with ZnO nanofibers prepared in Example 2 were examined by scanning electron microscopy before and after calcination. The results are as follows: Figure 1 The image shows scanning electron microscope (SEM) images of porous Co3O4 nanocubes embedded with ZnO nanofiber tubes before and after calcination. Figure 1 (c) shows the morphological characteristics of porous Co3O4 nanocubes embedded with ZnO nanofiber tubes before calcination, referring to... Figure 1 (c) As shown in the figure, the porous Co3O4 nanocubes embedded in the ZnO nanofiber tubes have a smooth surface structure and a diameter of about 250 nm before calcination. The nanocubes can be clearly seen to be encapsulated and evenly dispersed. Figure 1 (d) and Figure 2 (d) These are the morphological characteristics of porous Co3O4 nanocubes embedded with ZnO nanofiber tubes after calcination. As can be seen from the attached figure, the fiber diameter is reduced to about 100nm after calcination, and it presents a porous and rough appearance.

[0040] Transmission electron microscopy analysis was performed on the porous Co3O4 nanocube embedded ZnO nanofiber tubes prepared in Example 2. Figure 3 Transmission electron microscopy (TEM) analysis was performed on porous Co3O4 nanocubes embedded in ZnO nanofiber tubes prepared in Example 2. As shown in the figure, the porous Co3O4 nanocubes were well embedded in the nanofiber tubes, and the Zn element was uniformly distributed.

[0041] X-ray photoelectron spectroscopy analysis was performed on the porous Co3O4 nanocube embedded ZnO nanofiber tube prepared in Example 2. Figure 4 X-ray photoelectron spectroscopy (XPS) images of porous Co3O4 nanocubes embedded with ZnO nanofibers, referenced from... Figure 4 It can be seen that the peak positions of the obtained product are consistent with the peak positions of ZnO (1044.4eV and 1021.4eV) and Co3O4 (779.3eV and 794.3eV), which clearly indicates that the obtained product is a porous Co3O4 nanocube embedded with ZnO nanofiber tube.

[0042] X-ray single-crystal powder diffraction was performed on the porous Co3O4 nanocubes embedded with ZnO nanofiber tubes prepared in Example 2. Figure 5 The image shown is an X-ray single-crystal powder diffraction image of the porous Co3O4 nanocubes embedded with ZnO nanofiber tubes prepared in Example 2, with reference to... Figure 5 It can be seen that the peaks of the obtained product are consistent with those of ZnO (PDF#36-1451) and Co3O4 (PDF#42-1467), which clearly indicates that the obtained product is a porous Co3O4 nanocube embedded with ZnO nanofiber tube.

[0043] Example 3

[0044] This embodiment provides a porous Co3O4 nanocube embedded with ZnO nanofiber tube, the preparation process of which is as follows:

[0045] (1) Add 1.5 mmol of zinc nitrate hexahydrate to 4.5 mL of N,N dimethylformamide, stir to dissolve, then add 0.9 g of polyvinylpyrrolidone, which is recorded as the outer axis solution; add 0.1 mmol of ZIF-67 prepared in Example 1 to 4.5 mL of N,N dimethylformamide, sonicate for 10 min, stir for 10 min, then add 0.9 g of polyvinylpyrrolidone, which is recorded as the inner axis solution. Stir at 120 rpm / min for 12 h.

[0046] (2) The two solutions prepared above are spun using coaxial electrospinning technology under the conditions of humidity of 20% to 40%, voltage of 18kV, outer shaft speed of 0.0003mm / s and inner shaft speed of 0.0002mm / s.

[0047] (3) The nanofiber tubes obtained above were calcined in air at a temperature of 500℃ for 120 min at a heating rate of 2℃ / min. After cooling to room temperature, porous Co3O4 nanocubes embedded with ZnO nanofiber tubes were obtained, abbreviated as 0.1Co / Zn, and their morphological characteristics are shown in the figure below. Figure 2 As shown in (b).

[0048] Example 4

[0049] This embodiment provides a porous Co3O4 nanocube embedded with ZnO nanofiber tube, the preparation process of which is as follows:

[0050] (1) 1.5 mmol of zinc nitrate hexahydrate was added to 4.5 mL of N,N dimethylformamide and stirred until dissolved. Then, 0.9 g of polyvinylpyrrolidone was added, which was designated as the outer axis solution. 0.2 mmol of ZIF-67 prepared in Example 1 was added to 4.5 mL of N,N dimethylformamide, sonicated for 10 min, stirred for 10 min, and then 0.9 g of polyvinylpyrrolidone was added, which was designated as the inner axis solution. The stirring speed was 120 rpm / min, and the mixture was stirred for 12 h.

[0051] (2) The two solutions prepared above are spun using coaxial electrospinning technology under the conditions of humidity of 20% to 40%, voltage of 18kV, outer shaft speed of 0.0003mm / s and inner shaft speed of 0.0002mm / s.

[0052] (3) The obtained nanofiber tubes were calcined in air at a temperature of 500℃ for 120 min at a heating rate of 2℃ / min. After cooling to room temperature, porous Co3O4 nanocubes embedded with ZnO nanofiber tubes were obtained, abbreviated as 0.2Co / Zn, and their morphological characteristics are shown in the figure below. Figure 2 As shown in (c).

[0053] Example 5

[0054] This embodiment provides a porous Co3O4 nanocube embedded with ZnO nanofiber tube, the preparation process of which is as follows:

[0055] (1) 1.5 mmol of zinc nitrate hexahydrate was added to 4.5 mL of N,N dimethylformamide and stirred until dissolved. Then, 0.9 g of polyvinylpyrrolidone was added, which was designated as the outer axis solution. 0.4 mmol of ZIF-67 prepared in Example 1 was added to 4.5 mL of N,N dimethylformamide, sonicated for 10 min, stirred for 10 min, and then 0.9 g of polyvinylpyrrolidone was added, which was designated as the inner axis solution. The stirring speed was 120 rpm / min, and the mixture was stirred for 12 h.

[0056] (2) The two solutions prepared above are spun using coaxial electrospinning technology under the conditions of humidity of 20% to 40%, voltage of 18kV, outer shaft speed of 0.0003mm / s and inner shaft speed of 0.0002mm / s.

[0057] (3) The obtained nanofiber tubes were calcined in air at a temperature of 500℃ for 120 min at a heating rate of 2℃ / min. After cooling to room temperature, porous Co3O4 nanocubes embedded with ZnO nanofiber tubes were obtained, abbreviated as 0.4Co / Zn, and their morphological characteristics are shown in the figure below. Figure 2 As shown in (e).

[0058] Example 6

[0059] This embodiment provides a porous Co3O4 nanocube embedded with ZnO nanofiber tube, the preparation process of which is as follows:

[0060] (1) 1.5 mmol of zinc nitrate hexahydrate was added to 4.5 mL of N,N dimethylformamide and stirred until dissolved. Then, 0.9 g of polyvinylpyrrolidone was added, which was designated as the outer axis solution. 0.5 mmol of ZIF-67 prepared in Example 1 was added to 4.5 mL of N,N dimethylformamide, sonicated for 10 min, stirred for 10 min, and then 0.9 g of polyvinylpyrrolidone was added, which was designated as the inner axis solution. The stirring speed was 120 rpm / min, and the mixture was stirred for 12 h.

[0061] (2) The two solutions prepared above are spun using coaxial electrospinning technology under the conditions of humidity of 20% to 40%, voltage of 18kV, outer shaft speed of 0.0003mm / s and inner shaft speed of 0.0002mm / s.

[0062] (3) The obtained nanofiber tubes were calcined in air at a temperature of 500℃ for 120 min at a heating rate of 2℃ / min. After cooling to room temperature, porous Co3O4 nanocubes embedded with ZnO nanofiber tubes were obtained, abbreviated as 0.5Co / Zn, and their morphological characteristics are shown in the figure below. Figure 2 As shown in (f).

[0063] Comparative Example 1

[0064] This embodiment provides a porous hollow ZnO nanofiber tube, the preparation process of which is as follows:

[0065] (1) Add 1.5 mmol of zinc nitrate hexahydrate to 4.5 mL of N,N dimethylformamide, stir to dissolve, then add 0.9 g of polyvinylpyrrolidone, which is recorded as the outer axis solution; add 0.9 g of polyvinylpyrrolidone directly to 4.5 mL of N,N dimethylformamide, which is recorded as the inner axis solution. Stir at 120 rpm / min for 12 h.

[0066] (2) The two solutions prepared above are spun using coaxial electrospinning technology under the conditions of humidity of 20% to 40%, voltage of 18kV, outer shaft speed of 0.0003mm / s and inner shaft speed of 0.0002mm / s.

[0067] (3) The nanofiber tubes obtained above were calcined in air at a temperature of 500℃ for 120 min at a heating rate of 2℃ / min. After cooling to room temperature, porous ZnO nanofiber tubes were obtained, and their morphological characteristics are shown in the figure below. Figure 2 As shown in (a).

[0068] Comparative Example 2

[0069] This embodiment provides a porous hollow Co3O4 nanofilm, the preparation process of which is as follows:

[0070] (1) 0.3 mmol of the porous Co3O4 nanocubes prepared in Example 1 were dispersed in ethanol / deionized water, sonicated for 30 min, and 2 μL of the dispersed liquid was dropped onto a ceramic sheet and dried at room temperature overnight to obtain a porous hollow Co3O4 nanofilm.

[0071] Comparative Example 3

[0072] This embodiment provides a porous ZnCo2O4 / ZnO nanofiber tube, the preparation process of which is as follows:

[0073] (1) Add 1.5 mmol of zinc nitrate hexahydrate to 4.5 mL of N,N dimethylformamide, stir to dissolve, then add 0.3 mmol of ZIF-67 prepared in Example 1, and after ultrasonic dispersion, add 0.9 g of polyvinylpyrrolidone. Stir at 120 rpm / min for 12 h.

[0074] (2) The above-prepared solution is spun using uniaxial electrospinning technology under conditions of 20% to 40% humidity and 18kV voltage.

[0075] (3) The nanofibers obtained above were calcined in air at a temperature of 500℃ for 120 min at a heating rate of 2℃ / min. After cooling to room temperature, porous ZnCo2O4 / ZnO nanofiber tubes were obtained.

[0076] Comparative Example 4

[0077] This embodiment provides a porous ZnCo2O4 nanofiber, the preparation process of which is as follows:

[0078] (1) Add 1.5 mmol of zinc nitrate hexahydrate to 4.5 mL of N,N dimethylformamide and stir to dissolve. Then add 0.3 mmol of cobalt nitrate hexahydrate, sonicate to disperse evenly, and then add 0.9 g of polyvinylpyrrolidone. Stir at 120 rpm for 12 h.

[0079] (2) The above-prepared solution is spun using uniaxial electrospinning technology under conditions of 20% to 40% humidity and 18kV voltage.

[0080] (3) The nanofibers obtained above were calcined in air at a temperature of 500℃ for 120 min at a heating rate of 2℃ / min. After cooling to room temperature, porous ZnCo2O4 nanofibers were obtained.

[0081] Comparative Example 5

[0082] This embodiment provides a porous Co3O4@ZnO core-shell nanofiber, the preparation process of which is as follows:

[0083] (1) Add 1.5 mmol of zinc nitrate hexahydrate to 4.5 mL of N,N dimethylformamide, stir to dissolve, then add 0.9 g of polyvinylpyrrolidone, which is recorded as the outer axis solution; add 0.3 mmol of cobalt nitrate hexahydrate to 4.5 mL of N,N dimethylformamide, sonicate for 10 min, stir for 10 min, then add 0.9 g of polyvinylpyrrolidone, which is recorded as the inner axis solution. Stir at 120 rpm / min for 12 h.

[0084] (2) The two solutions prepared above are spun using coaxial electrospinning technology under the conditions of humidity of 20% to 40%, voltage of 18kV, outer shaft speed of 0.0003mm / s and inner shaft speed of 0.0002mm / s.

[0085] (3) The nanofiber tubes obtained above were calcined in air at a temperature of 500℃ for 120 min at a heating rate of 2℃ / min. After cooling to room temperature, porous Co3O4@ZnO core-shell nanofibers were obtained.

[0086] Comparative Example 6

[0087] This embodiment provides a porous Co3O4 nanocube embedded with ZnO nanofiber tube, the preparation process of which is as follows:

[0088] (1) Add 1.5 mmol of zinc nitrate hexahydrate to 4.5 mL of N,N dimethylformamide, stir to dissolve, then add 0.9 g of polyvinylpyrrolidone, which is designated as the outer axis solution; add 0.3 mmol of ZIF-67 prepared in Example 1 to 4.5 mL of N,N dimethylformamide, sonicate for 10 min, stir for 10 min, then add 0.9 g of polyvinylpyrrolidone, which is designated as the inner axis solution. Stir at 120 rpm / min for 12 h.

[0089] (2) The two solutions prepared above are used for coaxial electrospinning technology. The spinning is carried out under the conditions of humidity of 20% to 40%, voltage of 18kV, changing the pushing speed of the inner and outer shafts, with the outer shaft speed being 0.001mm / s and the inner shaft speed being 0.0005mm / s. The ratio of the pushing speed of the outer shaft to the inner shaft is 2:1.

[0090] (3) The nanofiber tubes obtained above were calcined in air at a temperature of 500℃ for 120 min at a heating rate of 2℃ / min. After cooling to room temperature, porous Co3O4 nanocube embedded ZnO nanofiber tubes were obtained.

[0091] Experimental Example

[0092] 1. Comparative Examples 3-6 were difficult to further test due to the poor properties of the prepared materials, specifically as follows:

[0093] Comparative Example 3 uses a blending technique to prepare porous ZnCo2O4 / ZnO nanofibers, which are solid fibers. Due to the ion exchange between zinc salt and cobalt salt, the ZIF-67 metal-organic framework prepared in Example 1 is completely destroyed after calcination, and cannot form the segmented morphology of Example 2.

[0094] Comparative Example 4 directly prepared porous ZnCo2O4 nanofibers using a blending technique, without employing porous metal-organic frameworks (MOFs). Therefore, its electrical conductivity was poor. Compared to the material prepared in Example 2, it had lower porosity and lower specific surface area, resulting in poorer gas storage and adsorption separation. There was no need for further testing.

[0095] Comparative Example 5 uses coaxial electrospinning technology to prepare porous Co3O4@ZnO core-shell nanofibers without using porous metal-organic frameworks (MOFs). Compared with the material prepared in Example 2, it has lower porosity and lower specific surface area, and therefore is also worse for gas storage and adsorption separation, and has extremely low response to ethylbenzene, so there is no need for further experiments.

[0096] Comparative Example 6 uses different feeding speeds to prepare Co3O4 nanocube embedded ZnO nanofiber tubes. The ratio of the outer axis speed to the inner axis speed is 2. Due to the fast feeding speed and the excessively high speed ratio, the spinneret is blocked during the electrospinning process. After calcination, the spun fibers are disordered and cannot achieve the morphology of the spun fibers obtained in Example 2.

[0097] 2. Performance Testing

[0098] (1) The porous Co3O4 nanocubes obtained in Examples 2-6 and Comparative Example 1 were embedded in ZnO nanofiber tubes and the ZnO nanofiber tubes were adhered to the surface of ceramic sheets with deionized water. After the materials were dried, gas-sensitive devices with different doping amounts were obtained.

[0099] (2) The porous Co3O4 nanocube film prepared in Comparative Example 2 was dispersed in ethanol / deionized water, sonicated for 30 min, and 2 μL of the dispersed liquid was dropped onto a ceramic sheet and dried at room temperature overnight to obtain a porous hollow Co3O4 nanofilm.

[0100] (3) Perform gas-sensitive testing on the device described in steps (1) and (2). Connect a picoammeter to apply a 5V bias voltage to the material, and connect a voltmeter to control the temperature. Test at 200-325℃ by introducing 50ppm ethylbenzene. The results are as follows: Figure 6 As shown, the porous Co3O4 nanocube embedded ZnO nanofiber tube obtained in Example 2 exhibits the highest sensitivity to 50 ppm ethylbenzene at 250°C.

[0101] The 0.3Co / Zn ratio obtained in Example 2, which exhibited the highest sensitivity to 50ppm ethylbenzene at 250℃, was selected. Sensitivity responses to various gases, including ethylbenzene, toluene, m-xylene, and formaldehyde, were then tested. The resulting sensitivity response radar graphs are shown below. Figure 7 As shown in (a), 0.3Co / Zn exhibits good selectivity.

[0102] Then, at 250℃ and 50ppm ethylbenzene, multiple cycles of testing were performed on the 0.3Co / Zn ratio, and the test results are as follows: Figure 7 As shown in (b), the 0.3Co / Zn prepared in Example 2 also has good repeatability.

[0103] The above examples and verification examples merely illustrate specific implementation methods of this application, and their descriptions are quite specific and detailed, but they should not be construed as limiting the scope of protection of this application. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the technical solution of this application, and these all fall within the scope of protection of this application.

Claims

1. A nanofiber tube with Co3O4 nanocubes embedded with ZnO, characterized in that, The nanofiber tubes are an inner axial solution obtained by dispersing ZIF-67 nanocubes in N,N dimethylformamide and adding polyvinylpyrrolidone, with Zn... 2+ The outer shaft solution obtained by dispersing N,N dimethylformamide and adding polyvinylpyrrolidone was spun simultaneously with the inner and outer shaft solutions using coaxial electrospinning technology, and the product was calcined in air using aluminum foil to collect the spun fibers. In the inner and outer axis solutions, ZIF-67 nanocubes and Zn 2+ The molar ratio is 0.06~0.33:1; The outer shaft pushing speed of the electrospinning is 0.0003 mm / s, and the inner shaft pushing speed is 0.0002 mm / s; The calcination temperature is 500℃, the calcination time is 120 min, and the heating rate is 2℃ / min.

2. The Co3O4 nanocube embedded ZnO nanofiber tube as described in claim 1, characterized in that, The porous Co3O4 nanocubes obtained by calcining the ZIF-67 nanocubes have a particle size of 100-200 nm.

3. The Co3O4 nanocube embedded ZnO nanofiber tube as described in claim 1, characterized in that, The nanofiber tubes have a width of 100~200 nm and a length of 100~500 μm.

4. The method for preparing Co3O4 nanocube embedded ZnO nanofiber tubes as described in any one of claims 1 to 3, characterized in that, Includes the following steps: ZIF-67 nanocubes were dispersed in NN dimethylformamide, and polyvinylpyrrolidone was added and stirred until homogeneous. This solution was denoted as the inner axis solution. Zn 2+ Disperse it in N,N dimethylformamide, add polyvinylpyrrolidone and stir to mix well, and record it as the outer axis solution; Among them, the inner-axis solution and the outer-axis solution contain ZIF-67 nanocubes and Zn 2+ The molar ratio is 0.06~0.33:1; Coaxial electrospinning technology is used to simultaneously spin solutions of the inner and outer shafts. The spinning high voltage is 18kV and the distance is 15cm. The outer shaft push speed of the electrospinning reaction is 0.0003mm / s and the inner shaft push speed is 0.0002mm / s. The reaction humidity is controlled at 20%~40%, and aluminum foil is used for receiving. The product was calcined in air at a temperature of 500°C for 120 min at a heating rate of 2°C / min to obtain hollow porous Co3O4 / ZnO nanofiber tubes.

5. The preparation method according to claim 4, characterized in that, The stirring time after adding polyvinylpyrrolidone to the inner and outer shaft solutions was 12 h.

6. The application of the Co3O4 nanocube embedded ZnO nanofiber tube as described in claim 1 as a material for preparing a gas sensor in ethylbenzene detection.

Citation Information

Patent Citations

  • ZnO / Co composite nano hollow fiber electromagnetic wave absorption material and preparation method thereof

    CN108753251A

  • Cobaltosic oxide / indium oxide nanotube composite film sensitive to acetone

    CN109678214A